Repetitive Erythropoietin Treatment Improves Long-Term Neurocognitive Outcome by Attenuating Hyperoxia-Induced Hypomyelination in the Developing Brain - Dewan, Monia Vanessa; Serdar, Meray; van de Looij, Yohan; Kowallick, Mirjam; Hadamitzky, Martin; Endesfelder, Stefanie; Fandrey, Joachim; Sizonenko, Stéphane V.; Herz, Josephine; Felderhoff-Müser, Ursula; Bendix, Ivo (Frontiers in Neurology, 2020)
Introduction: Preterm infants born before 28 weeks of gestation are at high risk of neurodevelopmental impairment in later life. Cerebral white and grey matter injury is associated with adverse outcomes. High oxygen levels, often unavoidable in neonatal intensive care, have been identified as one of the main contributing factors to preterm brain injury. Thus, preventive and therapeutic strategies against hyperoxia-induced brain injury are needed. Erythropoietin (Epo) is a promising and also neuroprotective candidate due to its clinical use in infants as erythropoiesis-stimulating agent. Objective: The objective of this study was to investigate the effects of repetitive Epo treatment on the cerebral white matter and long-term motor-cognitive outcome in a neonatal rodent model of hyperoxia-induced brain injury. Methods: Three-day old Wistar rats were exposed to hyperoxia (48 hours, 80 % oxygen). Four doses of Epo (5000 IU/kg body weight per day) were applied intraperitoneally from P3-P6 with the first dose at the onset of hyperoxia. Oligodendrocyte maturation and myelination were evaluated via immunohistochemistry and Western blot on P11. Motor-cognitive deficits were assessed in a battery of complex behaviour tests (Open Field, Novel Object Recognition, Barnes maze) in adolescent and fully adult animals. Following behaviour tests animals underwent post-mortem diffusion tensor imaging to investigate long-lasting microstructural alterations of the white matter. Results: Repetitive treatment with Epo significantly improved myelination deficits following neonatal hyperoxia at P11. Behavioural testing revealed attenuated hyperoxia-induced cognitive deficits in Epo-treated adolescent and adult rats. Conclusion: A multiple Epo dosage regimen protects the developing brain against hyperoxia-induced brain injury by improving myelination and long-term cognitive outcome. Though current clinical studies on short-term outcome of Epo-treated prematurely born children contradict our findings, long-term effects up to adulthood are still lacking. Our data support the essential need for long-term follow-up of preterm infants in current clinical trials.